Pressure induced mechanical, opto-electronics, and transport properties of ZnHfO3 oxide for solar cell and energy harvesting devices - Asif Mahmood; Shahid M Ramay; Waheed Al-Masry; Ateyah A Al-Zahrani; H M Shaikh (Materials Research Express, 2021)
Based on the density functional theory, we systematically investigate the effect of pressure on the mechanical, optoelectronic, and transport properties of ZnHfO _3 . The pressure has been employed up to 30 GPa in a step-size of 10 GPa. A slight variation in the lattice constant and Bulk modulus have been observed at the applied pressure steps. The electronic properties are significantly tuned by applying pressure. The calculated bandgap values slightly increase with increasing the pressure and its values start to decrease after the critical pressure of 20 GPa. More interestingly, a transition from indirect to direct band has been observed at the critical pressure. This transition of the bandgap is also justified by studying the optical properties like dielectric constant, refraction, and absorption at different pressure. Furthermore, we studied the electronic transport properties in terms of electrical conductivity, thermal conductivity, See-beck coefficient, and power factor at temperature (300–800 K). The calculated lattice thermal conductivities are low while the electrical conductivities and Seebeck coefficients are high at all pressure. Thus, the properties of the ZnHfO _3 show high potential for thermoelectric applications.